2021
DOI: 10.1038/s41598-021-85508-8
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal single particle steering generated through single particle entanglement

Abstract: In 1927, at the Solvay conference, Einstein posed a thought experiment with the primary intention of showing the incompleteness of quantum mechanics; to prove it, he employed the instantaneous nonlocal effects caused by the collapse of the wavefunction of a single particle—the spooky action at a distance–, when a measurement is done. This historical event preceded the well-know Einstein–Podolsk–Rosen criticism over the incompleteness of quantum mechanics. Here, by using the Stern–Gerlach experiment, we demonst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…The term 'steering' in quantum mechanics refers to the ability of one observer (Alice) to influence the state of a distant particle (Bob) through measurements made on her own particle. This phenomenon showcases the nonlocal nature of quantum entanglement [39]. It has been established that two successive SG experiments produce quantum nonlocality and quantum steering [40], whose relations with entanglement put a prominent footprint on our usual understanding of the experiment as a natural consequence of considering quantum correlations.…”
Section: Theory and Resultsmentioning
confidence: 89%
“…The term 'steering' in quantum mechanics refers to the ability of one observer (Alice) to influence the state of a distant particle (Bob) through measurements made on her own particle. This phenomenon showcases the nonlocal nature of quantum entanglement [39]. It has been established that two successive SG experiments produce quantum nonlocality and quantum steering [40], whose relations with entanglement put a prominent footprint on our usual understanding of the experiment as a natural consequence of considering quantum correlations.…”
Section: Theory and Resultsmentioning
confidence: 89%
“…Values that span from 2.5% up to 30.1% are observed for different levels of description of the setup (Figure 14I) [211]. Moreover, it has been reported that SPE is a resource for other kind of quantum information applications, for example quantum key distribution [223,224], quantum teleportation [225], state swapping [226], entanglement concentration [227], and single-photon steering [228,229].…”
Section: Single-particle Entanglementmentioning
confidence: 99%